Transient simulation and comparative assessment of a hydrogen production and storage system with solar and wind energy using TRNSYS. (22nd July 2022) - Wei, Donghui; Zhang, Liying; Alotaibi, Abdullah Alhumaidi; Fang, Junlong; Alshahri, Abdullah H.; Almitani, Khalid H.
Abstract: This paper uses the TRNSYS software to investigate the hourly energy generation potential, storage, and consumption via an electrolyzer and a fuel cell in the Canadian city of Saskatoon, which is a region with high solar and wind energy potential. For this purpose, a location with an area of 10, 000 m 2 was considered, in which the use of solar panels and vertical-axis wind turbines (VAWTs) were simulated. In the simulation, the solar panels were placed at specific distances, and the energy generation capacity, amount of produced hydrogen, and the energy available from the fuel cell were examined hourly and compared to the case with wind turbines placed at standard distances. The results indicated energy generation capacities of 1, 966, 084 kWh and 75, 900 kWh for the solar panels and the wind turbines, respectively, showing the high potential of solar panels compared to wind turbines. Moreover, the fuel cells in the solar and wind systems can produce 733, 077 kWh and 22, 629 kWh of energy per year, respectively, if they store all of the received energy in the form of hydrogen. Finally, the hourly rates of hydrogen production by the solar and wind systems were reported. Highlights: Solar panels and vertical-axis wind turbines are used to produce hydrogen. TRNSYS is employed to perform the simulations. Energy generation capacity of solar panels is 1, 966, 084 kWh. Energy generation capacity of wind turbines is 75, 900 kWh.